Assessment of Serum and Urine Neurophil Gelatinase- Associated Lipocalin (s-NGAL and u-NGAL) Level as a Predictive Factor of Disease Progression in Diabetic Nephropathy in Type 2 DM - Najafi, Laily; Keshtkar Rajabi, Shahin; Pirsaheb, Sondos; Keyvani, Hossein; Khajavi, Alireza; Shati, Mohsen; Hadavand, Fahimeh; Amouzegar, Atefeh (Iranian journal of kidney diseases, 2021)
Diabetic nephropathy (DN) is a major complication of diabetes Mellitus. Early detection and intervention of DN can slow its progression and improve patients' outcomes. Neutrophil gelatinase-associated lipocalin (NGAL) as a marker of tubular damage might become a useful biomarker for the evaluation of renal involvement in diabetic patients. We aimed to evaluate the serum and urine NGAL(s-NGAL and u-NGAL) in type 2 diabetic patients and its correlation with different stages of diabetic nephropathy. This cross-sectional study was designed on 198 subjects consisted of 50 controls and 148 type 2 diabetes patients (50 normoalbuminuric, 58 microalbuminuric, and 40 macroalbuminuric). The study was conducted with measuring s-NGAL and u-NGAL, albumin and spot urine creatinine were also measured. A highly increased level of s-NGAL was detected in macroalbuminuric group compared with controls, normoalbuminurics and microalbuminurics (P < .01). Highly raised u-NGAL levels were observed in macroalbuminurics in comparison with controls (P < .01). ROC curve demonstrated the best sensitivity and specificity of s-NGAL/u-NGAL for the macroalbuminuric state (sensitivity, 26% and 60%; specificity, 98% and 72%; respectively), in which the best cut-off points for the detection of macroalbuminuric state for s-NGAL/u-NGAL were 300 ng/mL and 71.4 ng/mL, respectively. Serum and urine-NGAL are elevated in type 2 diabetic patients, with or without albuminuria, s-NGAL level clearly correlates with severity of renal damage caused by DN and u-NGAL increases in macroalbuminuric state. S-NGAL could be a useful, noninvasive, available and practical test for evaluation of diabetic renal involvement. We could suggest u-NGAL as a probable predictor of macroalbuminuria.